COMPREHENSIVE INVESTIGATIONS OF ANCIENT HYDROGRAPHIC NETWORK OF WATERSHEDS: (on the pattern of Kasakh River watershed) (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
On the basis of analysis results of geophysical and hydrogeological investigations new data concerning ground water run off distribution of Kasakh River basin have been obtained. However, the vast watershed area and favorable natural realm for ground water development, the capacity of springs is not adequate. This can be explained by drainage of percolated water by buried valleys, out of which the Paleokasakh is one of the main underlava streams. On the basis of compiled underlava confining relief map of the Kasakh River watershed, new data concerning distribution of ground water run off network have been obtained. Assessment calculations of run off streams and infiltration out of Aparan reservoir have been conducted.
Keywords: Kasakh River; Paleokasakh; ground water run off distribution; geophysical and hydrogeological investigations